Making sense of conflicting messages of multiracial identity: a systematic review - Zamora, Tatiana I.; Padilla, Amado M. (Frontiers in Psychology, 2024)
Ethnic-racial identity (ERI) development includes how individuals' experiences, beliefs, and attitudes influence understanding of group membership. Messages about race, from multiple ecosystems, influence this identity development and how individuals make sense of their ERI. There has been a shift in ERI research to focus on Multiracial populations, however, most of the research focus is on Black/ white biracial and general, non-specified Multiracial populations. The ERI development process and experience for persons of other Multiracial backgrounds, such as AfroLatinx, is not as extensively studied. This systematic literature review focuses on understanding the current conceptualization of ERI development for non-Black/white biracial and general Multiracial populations in the United States. Common themes that emerge include the importance of spaces, conflicting social messages directed at Multiracial individuals, and coping responses used by Multiracial persons when faced with challenges.